Cinema e linguagem: As transformações perceptivas e cognitivas - de Oliveira, Robespierre [UNESP]; Colombo, Angélica Antonechen (My University, 2014)
The present study has aimed to investigate the emergence of film language and aesthetic character of the film and how their characteristics influence the forms of artistic apprehension by society, as a result of seeking the idea that this film aesthetic experience transformed the perception of the viewers. Christian Metz and his theory of language in the film were chosen as the theoretical framework, and as methodology we used bibliographic research.
Cinema and language: Perceptual and cognitive changes
Keywords: Cinema; Cognition; Language; Perception